Reducing dietary lipopolysaccharides to slow progression of cognitive impairment and Alzheimer’s disease - Blake, Steven Michael; Baroni, Luciana; Blake, Catherine Peterson; Harding, Thomas; Piboolnurak, Panida; Harding, Maile; Grant, William Burgess (Journal of Brain Sciences, 2024)
We hypothesize that a dietary reduction of lipopolysaccharide (LPS) could reduce risk and slow progression of cognitive impairment and Alzheimer’s disease by reducing neuroinflammation. LPS is a component of the highly inflammatory cell membrane of Gram-negative bacteria. LPS and inflammatory cytokines are elevated in Alzheimer’s disease, both in plasma and in the central nervous system. Inflammatory cytokines, triggered by LPS in food, can enter the brain via active transport and induce microglial activation and inflammatory damage, including loss of synapses and neurons. Excess LPS and inflammatory cytokines can also induce blood-brain barrier damage and increase amyloid-β production. The highest dietary sources of LPS are processed meat and dairy products, which can rapidly raise levels of plasma LPS within one to two hours. For example, there was a 65-fold increase in plasma LPS after eating a thin-crust cheese pizza. The LPS in these foods is transported via chylomicrons into the bloodstream. Smaller amounts of LPS from colonic microbiota do not account for the sharp postprandial increase of plasma LPS. Once in the bloodstream, LPS can increase inflammatory cytokines 2-fold to 68-fold within two hours. LPS increases cytokines via LPS binding protein and cluster of differentiation-14, triggering toll-like receptor-4, and activating nuclear factor kappa-B. Nuclear factor kappa-B can increase cytokine levels, including interleukin-1-beta, interleukin-6, and tumor necrosis factor-alpha. Practical implications: Even low plasma levels of LPS can reduce cognition. Decreasing brain inflammation by reducing dietary LPS can lower risk of cognitive impairment and dementia.